2021
DOI: 10.3390/su13020692
|View full text |Cite
|
Sign up to set email alerts
|

Information Technologies for Welfare Monitoring in Pigs and Their Relation to Welfare Quality®

Abstract: The assessment of animal welfare on-farm is important to ensure that current welfare standards are followed. The current manual assessment proposed by Welfare Quality® (WQ), although being an essential tool, is only a point-estimate in time, is very time consuming to perform, only evaluates a subset of the animals, and is performed by the subjective human. Automation of the assessment through information technologies (ITs) could provide a continuous objective assessment in real-time on all animals. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 121 publications
1
23
0
2
Order By: Relevance
“…Nevertheless, the developments achieved in the last two decades in precision livestock farming (PLF), with close collaboration between researchers associated with engineering and the livestock sector, have driven a significant evolution in animal welfare assessment. PLF has developed rapidly in recent years, and animal welfare can be objectively assessed in real-time using a wide variety of indicators [ 11 ]. This assessment of welfare indicators is already possible, and it is expected to undergo extraordinary progress in the near future for livestock production.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the developments achieved in the last two decades in precision livestock farming (PLF), with close collaboration between researchers associated with engineering and the livestock sector, have driven a significant evolution in animal welfare assessment. PLF has developed rapidly in recent years, and animal welfare can be objectively assessed in real-time using a wide variety of indicators [ 11 ]. This assessment of welfare indicators is already possible, and it is expected to undergo extraordinary progress in the near future for livestock production.…”
Section: Introductionmentioning
confidence: 99%
“…This complexity may explain why a wide range of PLF technologies still require further validation. In their study, Larsen et al (2021) found that only 23% of publications related to PLF in pigs were properly validated, and a recent review indicated that only 14% of commercially available sensors in dairy cattle were externally validated (Stygar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Knierim et al ( 43) also questioned whether health-centered welfare assessment protocols that are implemented in the dairy industry, such as the US-based FARM program (https://nationaldairyfarm.com/farmanimal-care-version-4-0/) or the UK-based AssureWel protocol (http://www.assurewel.org/dairycows) sufficiently take societal expectations into account, which often relate to naturalness for dairy cattle. Perhaps with the rapid advancements in the use of automated sensor technologies for monitoring livestock behavior and condition, such information may be incorporated in welfare assessment protocols in the future (44)(45)(46). Such measures could be added to the protocol by using the step-wise approach we proposed.…”
Section: Discussionmentioning
confidence: 99%